Image trap : M.G. Ramachandran in film and politics - "Pandian, M. S. S." (New Delhi, 2015)
The Image Trap analyses the phenomenon of M.G. Ramachandran (M.G.R), the legendary film star-cum-politician of Tamil Nadu, as a modern-day political myth. This book offers fascinating details about the extent to which MGR was successful in creating a stereotypical cinematic persona and what repercussions it had on Tamil Nadu. Delineating the cultural elements that were meticulously mobilised to constitute MGR's on-screen image, it analyses the popularity he enjoyed among the poor whose interests he constantly violated. This is done by means of what Pandian termed as constructed biographies which are popular narratives that ingeniously present the cinematic as real. It brings out the interface and interplay between the media and political processes. A blend of essay writing, political rhetoric and scholarship, the book features the complete filmography of MGR and is a must for understanding the contemporary politics of the state.
Keywords: "Ramaccantiran2, Em. Ji"